Pengaruh Suku Bunga, Nilai Tukar Rupiah, Inflasi Dan Harga Minyak Dunia Terhadap Ihsg Di Bei - Sumitra, Reagan Wijaya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research is to analyze the influence of macroeconomic towards composite share price index in Indonesia. This research is an explanatory research with quantitative paradigm. This research is using secondary data and the sample determined by full sampling technique based on time series date that has been accessed on official website of Bank Indonesia and finance yahoo year 2013 to 2017 which is consist of 60 samples. This research used multiple linier regression analysis. Based on classic assumption test, the datas in this research has been comply the assumption. Based on the multiple linier regression test, exchange rates and crude oil price has positive effect, whereas the inflation and interest rates has negative effect on composite share price index. Based on R2 test, 73,3 % of composite share price index influenced by interest rates, exchange rates, inflation and crude oil price. Based on F test, macro economic factors simultantly influence composite share price index. Based on t test, interest rates and exchange rates has a significant effect on composite share price index, whereas the inflation and crude oil price did not have significant effect on composite share price index.